Alternatives to patient specific verification measurements in proton therapy: a comparative experimental study with intentional errors. (17th October 2018) - Matter, M; Nenoff, L; Meier, G; Weber, D C; Lomax, A J; Albertini, F
Abstract: Patient specific verification (PSV) measurements for pencil beam scanning (PBS) proton therapy are resource-consuming and necessitate substantial beam time outside of clinical hours. As such, efforts to safely reduce the PSV-bottleneck in the clinical work-flow are of great interest. Here, capabilities of current PSV methods to ensure the treatment integrity were investigated and compared to an alternative approach of reconstructing the dose distribution directly from the machine control- or delivery log files with the help of an independent dose calculation (IDC). Scenarios representing a wide range of delivery or work-flow failures were identified (e.g. error in spot position, air gap or pre-absorber setting) and machine files were altered accordingly. This yielded 21 corrupted treatment files, which were delivered and measured with our clinical PSV protocol. IDC machine- and log file checks were also conducted and their sensitivity at detecting the errors compared to the measurements. Although some of the failure scenarios induced clinically relevant dose deviations in the patient geometry, the PSV measurement protocol only detected one out of 21 error scenarios. However, 11 and all 21 error scenarios were detected using dose reconstructions based on the log and machine files respectively. Our data suggests that, although commonly used in particle therapy centers, PSV measurements do a poor job detecting data transfer failures and imperfect delivery machine performance. Machine- and log-file IDCs have been shown to successfully detect erroneous work-flows and to represent a reliable addition to the QA procedure, with the potential to replace PSV.